1991
DOI: 10.1172/jci115252
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a monoclonal kappa chain of the V kappa IV subgroup in the kidney and plasma cells in light chain deposition disease.

Abstract: That structural abnormalities may be responsible for nonamyloid immunoglobulin (Ig) light chain deposition disease (LCDD) is suggested by previous results of Ig biosynthesis studies, but this hypothesis was not documented at the molecular level. We report on the first complete primary sequence deduced from cDNA analysis of a K light chain responsible for LCDD associated with an apparently nonsecretory myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 38 publications
1
57
0
Order By: Relevance
“…and when deposited, truncated heavy chains), in such a case, we recently demonstrated that the LC produced hy the hone marrow cells and that found in the tissue deposits were identical and hore several point mutations in the V.-J^ region, one of which resulted in Nglycosylation (at position +70) that occurred in the myeloma eells. thus suggesting that the abnormality responsible for tissue deposition is at the LC level [10]. In the other patients, the pla.sma cells synthesized normal-size LC that were secreted as monomers and dimers.…”
Section: Discussionmentioning
confidence: 97%
“…and when deposited, truncated heavy chains), in such a case, we recently demonstrated that the LC produced hy the hone marrow cells and that found in the tissue deposits were identical and hore several point mutations in the V.-J^ region, one of which resulted in Nglycosylation (at position +70) that occurred in the myeloma eells. thus suggesting that the abnormality responsible for tissue deposition is at the LC level [10]. In the other patients, the pla.sma cells synthesized normal-size LC that were secreted as monomers and dimers.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the AL proteins we have studied contain carbohydrate [9], but we have been unable to establish if the glycosylation has anything to do with the fibrillogenic nature of AL chains. Glycosylation may play a direct role in tissue precipitation due to the binding to collagen and decreased catabolism of light chains [25].…”
Section: Discussionmentioning
confidence: 99%
“…43 It has been reported that somatic mutation of the V -IV family gene, which was deposited in the kidney, resulted in a potential N-glycosylation site. 44 However, one patient (UPN-AK4), whose V gene had such a potentially Nglycosylated site, did not have renal dysfunction. Thus, we could not find a clear correlation between the primary sequence of IgL and nephropathy.…”
Section: Comparison Of the Clinical Features And Igl Sequencesmentioning
confidence: 98%
“…In the light chain deposition disease which reportedly causes renal dysfunction, it has been suggested that an unusual sequence and/or glycosylation of the -chain is related to the pathogenesis. 43,44 However, in the patients with renal dysfunction, no common structure of IgL was observed. A potential N-glycosylation site, Asn-Phe-Thr at codon 70, 44 was found in only one patient AK4 (Figure 1), whose renal function was normal.…”
Section: Relationship Between Clinical Features and The Igl Sequencesmentioning
confidence: 99%
See 1 more Smart Citation